Sweep seed drill for intercultural operation along with sowing of soybean (Glycine max) crop - SINGH, DEVVRAT; RAMTEKE, RAJKUMAR; VYAS, A K; KHAN, I R (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted to study the effect of planting by tractor-drawn sweep seed drill, on growth and yield performance of soybean, weed population and economics. A Tractor drawn sweep seed drill, attachable on 30 PTO hp tractor was conceived, fabricated and validated for facilitating weeding along with sowing operations on the field prepared for soybean crop. The use of developed seed drill leads to saving of one pass tillage and one weeding operation in the initial growth period. In this way, approximately ` 3 000/ha/season could be saved from the total expenditure. The simultaneous tillage and sowing operation by the machine helps to maintain higher plant population (25.22–34.55%). This also leads to reduction of weeds (59.91– 68.37%) as compared to flat sowing method. Thus, the use of sweep seed drill curtails the cost on post sowing weedicides along with seed bed preparation as one operation of cultivator. Result of the study indicated that crop planted by the sweep seed drill showed yield increase from 7.78 to 16.46% as compared to normal seed drill. It is suggested to get tractor-operated sweep seed drill manufactured with an adjustable frame which could hold sweeps at the rear end of the frame of the seed drill and the tines for dropping seeds on the front of the seed drill frame to ensure better field operation.